1976
DOI: 10.1090/s0002-9904-1976-13976-6
|View full text |Cite
|
Sign up to set email alerts
|

A nonstandard representation for Brownian motion and Itô integration

Abstract: A number of authors have attempted to apply Nonstandard Analysis to Probability Theory. Unfortunately, the nonstandard reformulations heretofore proposed have retained most of the essential difficulties inherent in the standard formulations. As a result, the application of nonstandard techniques has met with limited success. Hersh [4] produced a nonstandard analogue of Wiener measure. His "measure", however, is not countably additive; moreover, it is supported on a countable subset of C([0, 1]). Using a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(110 citation statements)
references
References 6 publications
2
108
0
Order By: Relevance
“…However, it should be noted that not even all internal subsets of G ω are necessarily measurable with respect to λ f × λ g . Fortunately, the following fact is still true-see [4] or [1].…”
Section: The Algebra Of Measures On a Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that not even all internal subsets of G ω are necessarily measurable with respect to λ f × λ g . Fortunately, the following fact is still true-see [4] or [1].…”
Section: The Algebra Of Measures On a Groupmentioning
confidence: 99%
“…Besides the original Robinson's book [25], the standard general reference are the monographs [1] and [28]. For Loeb measure also the original papers by Loeb [18][19][20][21], as well as [4], [5], [13], [14] and the survey [6] by Cutland can be consulted. Some recent developments are reflected in [17], [3] and the survey [26] by Ross.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson [2], Hoover and Perkins [9], Keisler [10], Lindstrøm [11], a few to mention, used Loeb's [12] approach to develop basic nonstandard stochastic analysis and in particular, the nonstandard Itô calculus. Loeb [12] also presents the construction of a Poisson processes using nonstandard analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Loeb [12] also presents the construction of a Poisson processes using nonstandard analysis. Anderson [2] showed that Brownian motion can be constructed from a hyperfinite number of coin tosses, and provides a detailed proof using a special case of Donsker's theorem. Anderson [2] also gave a nonstandard construction of stochastic integration with respect to his construction of Brownian motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation